(untitled) - DWI NOVITASARI, SHELI (RETAIN : Journal of Research in English Language Teaching, 2013)
Membaca adalah salah satu dari empat kemampuan penting yang harus dikuasai oleh siswa. Dalam pendidikan, membaca lebih ditekankan daripada yang lain terutama untuk pemahaman bacaan. Meskipun membaca lebih ditekankan daripada kemampuan lainnya, ajaran membaca di banyak sekolah tidak memfasilitasi siswa untuk menjadi terampil dalam membaca (Heaton: 1975). Kemampuan siswa masih dinilai kurang. Sebagian besar siswa dapat memecahkan kode kata-kata dalam teks dengan baik, tetapi mereka tidak bisa memahami makna teks dengan baik. Dengan demikian, guru harus menggunakan cara yang tepat membaca berdasarkan kebutuhan siswa dan juga harus berguna bagi siswa. Dalam hal ini, guru perlu Three Level Guide Strategy sebagai strategi yang tepat untuk mengajarkan pemahaman membaca. Dalam strategi ini, guru harus membuat guide statements, yang dibagi menjadi tiga tingkatan: (1) Pemahaman Literal, (2) Interpretasi, (3) Aplikasi (Vacca, 2004:339). Strategi ini bertujuan untuk membantu siswa menemukan informasi dari teks yang mereka baca, menghubungkan ide-ide yang ada di setiap paragraf, memahami maksud yang disampaikan penulis, dan menerapkan informasi berdasarkan pengetahuan mereka. Strategi ini membantu siswa untuk fokus dan berpikir lebih kritis. Jenis penelitian ini adalah kuantitatif eksperimental. Oleh karena itu, data yang ada berupa angka. Populasi dalam penelitian ini adalah siswa kelas XI SMA Negeri 1 Driyorejo, sedangkan sampelnya, kelas XI IPA 2 sebagai kelompok eksperimen dan XI IPA 3 sebagai kelompok kontrol. Untuk memperoleh data, kedua kelompok diberi tes, try-out, pre-test, dan post-test. Dari data yang diperoleh, peneliti menggunakan perhitungan statistik. Peneliti menggunakan rumus t-test untuk menganalisis perbandingan nilai post-test antara kelompok eksperimen dan kontrol untuk melihat perbedaan yang signifikan. Hasil penelitian menunjukkan bahwa skor post-test kelompok eksperimen lebih tinggi daripada kelompok kontrol. Oleh karena itu, dapat disimpulkan bahwa hipotesis nol penelitian ini ditolak, sedangkan hipotesis alternatif diterima. Kesimpulannya, Three Level Strategy efektif untuk mengajarkan pemahaman membaca teks report untuk siswa kelas XI karena ada perbedaan yang signifikan dari skor antara siswa yang diajarkan menggunakan Three Level Strategy dengan yang tidak. Kata Kunci: Three Level Guide Strategy, pemahaman membaca, teks report. Abstract Reading is one of the four important skills that has to be mastered by students in all level of learners. In education, reading is more emphasized than others especially for reading comprehension. Although reading is more emphasized than the other skills, the teachings of reading in many schools do not facilitate students to be skilled in reading (Heaton: 1975). The students’ ability is still insufficient. Mostly students can decode the words in the texts well, but they cannot understand and get the meaning of the text well. Thus, the teacher has to use an appropriate way to teach reading based on the students’ need and also must be helpful for students. In this case, the teacher needs Three Level Guide Strategy as an appropriate strategy to teach reading comprehension. In this strategy, the teacher writes the guides in the form of series of statements not questions, which are divided into three levels; (1) Literal recognition; (2)Interpretation; (3) Application (Vacca, 2005:339). This study aims to help students locate the information from the tect they read, making link between the ideas, interprets what the author means, and then apply the information based on their prior knowledge and opinion. It guides students to focus and think more critically while they read the texts. This is experimental quantitative study. Therefore, the data were the form of numbers. The population was the eleventh graders of SMA Negeri 1 Driyorejo, while the samples were class XI IPA 2 as the experimentalgroup and XI IPA 3 as the control group. To get the data, those two groups were given tests; try-out, pre-test, and post-test. From the data, the researcher calculated by using statistical computation. The researcher used t-test formula to analyze the comparison of the post-test scores between the experimental and control group in order to see the significant difference. The result of the study showed that the post-test scores of the experimental group were higher than the control group. Therefore, it can be concluded that the null hypothesis of this study was rejected, while the alternatives hypothesis was accepted. In conclusion, The Three Level Guide Strategy is effective to teach reading comprehension of report texts for the eleventh graders since there is a significant difference of the scores between they who were taught by using Three Levels Guide Strategy and they who were not. Moreover, it can be the alternative strategy for the English teachers to teach reading comprehension. Keyword: Three Level Guide Strategy, Reading Comprehension, Report Texts